2013
DOI: 10.1093/cid/cit270
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Small-Colony Variants Are Independently Associated With Worse Lung Disease in Children With Cystic Fibrosis

Abstract: Infection with SCV S. aureus was independently associated with worse CF respiratory outcomes in this pediatric cohort. As many clinical microbiology laboratories do not specifically detect S. aureus SCVs, validation and extension of these findings would require widespread changes in the usual laboratory and clinical approaches to these bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(149 citation statements)
references
References 27 publications
7
139
2
1
Order By: Relevance
“…In a CF center in the United States, 100 children with CF, of whom 24 had SCV S. aureus, were followed for an average of 1.7 years. 95 Those with SCV strains had lower lung function at the beginning and end of the study, but they had a similar rate of pulmonary exacerbations. Notably, 33% of the children with SCV strains did not have normal-colony S. aureus strains, which suggests that these children would not have been identified as infected with S. aureus had SCV strains not been sought.…”
Section: Ic4 Small Colony Variant (Scv) S Aureusmentioning
confidence: 90%
See 1 more Smart Citation
“…In a CF center in the United States, 100 children with CF, of whom 24 had SCV S. aureus, were followed for an average of 1.7 years. 95 Those with SCV strains had lower lung function at the beginning and end of the study, but they had a similar rate of pulmonary exacerbations. Notably, 33% of the children with SCV strains did not have normal-colony S. aureus strains, which suggests that these children would not have been identified as infected with S. aureus had SCV strains not been sought.…”
Section: Ic4 Small Colony Variant (Scv) S Aureusmentioning
confidence: 90%
“…Notably, 33% of the children with SCV strains did not have normal-colony S. aureus strains, which suggests that these children would not have been identified as infected with S. aureus had SCV strains not been sought. 95 In addition, 2 pairs of subjects had the same SCV strains, suggesting possible transmission of SCVs between children with CF.…”
Section: Ic4 Small Colony Variant (Scv) S Aureusmentioning
confidence: 99%
“…Displacement of the natural upper airway microbes (Streptococcus pneumoniae, Haemophilus influenzae, and Staphylococcus aureus) by Pa is a hallmark of CF pulmonary disease progression (O'Sullivan & Freedman, 2009). Deep airway infections due to S. aureus and other oral organisms have also been shown to contribute to the microbial burden and inflammation that causes a decline in respiratory function (Flume & Van Devanter, 2012;Foweraker, 2009;Wolter et al, 2013). However, 60-85% of the CF population is colonized by Pa (FitzSimmons, 1993;Mahadeva et al, 1998).…”
Section: Clinical Characteristics Of Pseudomonal Infection In the Airmentioning
confidence: 99%
“…Auxotrophy associated with bacterial small-colony-variants in other chronic infections: a sign of bacterial endosymbiosis Bacterial small-colony-variants (SCV) isolates of S. aureus, S. maltophilia, and B. cepacia have frequently been found in the airway secretions of CF patients (Anderson et al, 2007;Haussler et al, 1999Haussler et al, , 2003aProctor et al, 2006;Wolter et al, 2013). Moreover, many examples of bacterial SCV associated chronic infections other than CF suggest translocation of bacterial commensals to otherwise ''sterile'' anatomic environments, even in immunocompetent hosts who have received adequate antimicrobial treatment.…”
Section: Cf Pa Evasion Of Host Defenses By Inactivation Of Arginine Bmentioning
confidence: 99%
“…It is important to use special culture conditions for the isolation of SCVs, because these phenotypes are easily overgrown on standard agar by cocolonizing bacteria due to their slow growth and their small colony size and are therefore difficult to isolate. Furthermore, it is of special interest to improve culture conditions for these phenotypes, because they are associated with chronic or persistent infections and with decreased pulmonary function and are more resistant to antibiotics than the normal phenotype (9)(10)(11)(12)(13)(14). Whereas all laboratories reported that they informed the clinic about pathogens with mucoid phenotypes, the culture of SCVs was reported by only 70% of investigators.…”
mentioning
confidence: 99%